Pendampingan Anak-anak Mengenal Sejarah Lokal Berbasis Digital Folklore di Kecamatan Medan Barat - Windari, Fenny; Ikhwal, Muhammad; Wahyuni, Sri; Putra, Rizaldy; Rosramadhana, Rosramadhana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The child ? support activity in an introduction to local history-based folklore aims to increase the interest of children in the race-based reading park, to increase children?s knowledge of local history or folklore, and to instill moral values in the story. The method of execution used in such devoted activities is the preparation, application, and application stage. The result of such devotion is the 5 M ( Reading, Chanting, Watching, Writing and Reprogramming) of the cause for learning about the folklore in northern Sumatra. Further increase children?s creativity by training them to create simple posters of the folklore that they already know about. The next stage of recording sounds to children. This was done because in the process of making each a video character. The sleuthing created an app with posters an a video based on a digital focus lore.